2016
DOI: 10.1097/nne.0000000000000194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simulation and Clinical Experience on Self-efficacy in Nursing Students

Abstract: This study compared the effect of simulation and clinical experience timing on self-confidence/self-efficacy for the nursing process. Using a randomized, double-crossover design, self-efficacy was measured 3 times. Although self-efficacy was significantly higher at time 1 for students who had clinical experience, there was no difference between the groups at the end of the course (time 2). Thus, simulation increased self-confidence/self-efficacy equivalently if placed either before or after clinical experience. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
7
21
0
14
Order By: Relevance
“…The slight improvement in communication self-efficacy after the program is likely due to the therapeutic and non-therapeutic communication training and role-playing exercises. Education utilizing simulated patients that help students feel more self-confident as well as continuous, regular communication training seems to be necessary to improve communication self-efficacy [30,64].…”
Section: Discussionmentioning
confidence: 99%
“…The slight improvement in communication self-efficacy after the program is likely due to the therapeutic and non-therapeutic communication training and role-playing exercises. Education utilizing simulated patients that help students feel more self-confident as well as continuous, regular communication training seems to be necessary to improve communication self-efficacy [30,64].…”
Section: Discussionmentioning
confidence: 99%
“…There were no superiority trials among the six included RCTs; however, two studies were identified as noninferiority studies Level 1, Level 3. There were no statistically significant differences in knowledge (p = 0.478), clinical competency (p = 0.688), critical thinking and readiness for practice (NCLEX) (p = 0.737) for students undertaking traditional placements versus students substituting 25% and 50% of clinical Two of the RCTs appeared to be sufficiently powered: Hayden et al (2014) and Watson et al (2012), two were potentially underpowered based on information given (Blackstock et al, 2013;Schlairet & Pollock, 2010) and two RCTs were samples of convenience (Kimhi et al, 2016;Soccio, 2017). Three of these studies used validated tools for their primary outcome.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…Além disso, estudos como este mostra que estudantes após vivenciarem simulação realística apresentam melhora da autoconfiança (Ferreira et al, 2018;Nascimento & Magro, 2018;Smith & Roehrs, 2009). Diferentes estudos referem que os participantes apresentaram níveis elevados de autoconfiança (Smith & Roehrs, 2009;Kimhi, Reishtein, Cohen, Hurvitz, & Avraham, 2016 enfermagem mesmo entre aqueles que já experienciaram situações clínicas reais (Kimhi et al, 2016). Os resultados apresentados na Tabela 2, a qual apresenta as respostas atribuídas às duas dimensões da ESEAA, demonstram que não houve diferença estatisticamente significativa no cenário, demostrando que é possível utilizar paciente-ator com baixo custo, garantindo uma simulação de alta fidelidade.…”
Section: Discussionunclassified